Strategies for Developing Speaking Skills by Utilizing Language Learning Podcasts - Mohzana, Mohzana (International Journal of Language and Ubiquitous Learning, 2024)
Background. Speaking skill development is a crucial aspect of language learning. This study aims to explore the effectiveness of podcasts as an innovative strategy in the development of speaking skills, opening up opportunities for further research into more progressive language learning methods. Purpose. The study aims to provide an in-depth understanding of the role of podcasts in the development of speaking skills and explore the potential of innovative language learning methods. Method. A quantitative approach with survey method was used, involving 25 Arabic and English language students as the sample. Data was collected through a questionnaire distributed through Google Form, with analysis using the Miles Huberman approach and data visualization in the form of charts to understand the percentage of responses. Results. From the questionnaire results, it appears that podcasts play an important role in the development of speaking skills. The varying frequency of use reflects the high level of student interest and engagement with the audio material. While most respondents saw the benefits of podcasts in improving confidence and language acquisition, the neutral responses provided opportunities for adjustments to the learning approach. Conclusion. The conclusions of this study provide a basis for designing more targeted learning strategies, considering the diversity of student experiences and needs.